Berbagai Kesalahpahaman Kinerja Konselor Sekolah Menurut Persepsi Guru Bidang Studi - Widyastuti, Dwi Yogianti Kurnia; Awalya, Awalya (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
The purpose of this study was to determine how perceptions of teachers' performance against misunderstandings counselor at Senior High School in Purbalingga . This type of research used in this research is descriptive quantitative research. Data collector using a Likert scale with the number of 65-point declaration has been tested before. Data analysis technique use descriptive percentage. Results of research conducted, shows that teachers of high school in the country Purbalingga district academic year 2015/2016 in general understands and has a positive perception of the school counselor. Any 8 points misconception is used, there are seven points of misunderstanding the category of very low perceptions of teachers to the misconception that the counselor's task in guidance and counseling equated with or separated entirely from education, perception of teachers to the misconception that the school counselor is a police school , the perception of teachers against the misconception that guidance and counseling restricted to clients only certain perception of teachers against the misconception that school counselors in implementing guidance and counseling services only work alone, the perception of teachers against the misconception that a job as a counselor can performed by anyone, the perception of teachers against the misconception that the work of the counselor should be immediately seen, the perception of teachers to the misconception that the counselor leveler ways of solving the problem for all clients. As well as one point in the lower categories of teachers' perceptions of the misconception that guidance and counseling counselor regarded solely as an advisory process.